A new assessment in total and extreme rainfall trends over central and southern Peruvian Andes during 1965-2010 - Heidinger, H (2018)
This research was funded by the Consultative Group for International Agricultural Research (CGIAR) Research Program on Climate Change, Agriculture and Food Security (CCAFS). H. Heidinger acknowledges CONCYTEC (Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica) for partially funding her doctoral studies at UCSB. The authors would like to acknowledge the anonymous reviewers for their constructive comments